Electrospun fibers and sorbents as a possible basis for effective composite wound dressings - Saul Alvarez-Suarez, Alan; Dastager, Syed G.; Bogdanchikova, Nina; Grande, Daniel; Pestryakov, Alexey; Carlos Garcia-Ramos, Juan; Lizeth Perez-Gonzalez, Graciela; Juarez-Moreno, Karla; Toledano-Magana, Yanis; Smolentseva, Elena; Antonio Paz-Gonzalez, Juan; Popova, Tatiana; et al. (Micromachines, 2020)
Skin burns and ulcers are considered hard-to-heal wounds due to their high infection risk. For this reason, designing new options for wound dressings is a growing need. The objective of this work is to investigate the properties of poly (epsilon-caprolactone)/poly (vinyl-pyrrolidone) (PCL/PVP) microfibers produced via electrospinning along with sorbents loaded with Argovit (TM) silver nanoparticles (Ag-Si/Al2O3) as constituent components for composite wound dressings. The physicochemical properties of the fibers and sorbents were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and inductively coupled plasma optical emission spectroscopy (ICP-OES). The mechanical properties of the fibers were also evaluated. The results of this work showed that the tested fibrous scaffolds have melting temperatures suitable for wound dressings design (58-60 degrees C). In addition, they demonstrated to be stable even after seven days in physiological solution, showing no macroscopic damage due to PVP release at the microscopic scale. Pelletized sorbents with the higher particle size demonstrated to have the best water uptake capabilities. Both, fibers and sorbents showed antimicrobial activity against Gram-negative bacteria Pseudomona aeruginosa and Escherichia coli, Gram-positive Staphylococcus aureus and the fungus Candida albicans. The best physicochemical properties were obtained with a scaffold produced with a PCL/PVP ratio of 85:15, this polymeric scaffold demonstrated the most antimicrobial activity without affecting the cell viability of human fibroblast. Pelletized Ag/Si-Al2O3-3 sorbent possessed the best water uptake capability and the higher antimicrobial activity, over time between all the sorbents tested. The combination of PCL/PVP 85:15 microfibers with the chosen Ag/Si-Al2O3-3 sorbent will be used in the following work for creation of wound dressings possessing exudate retention, biocompatibility and antimicrobial activity.
Keywords: electrospinning; poly (epsilon-caprolactone); poly (vinyl pyrrolidone); silver sorbents; wound dressings

Low-cost gelatin/collagen scaffolds for bacterial growth in bioreactors for biotechnology - Pompa-Monroy, Daniella Alejandra; Vera-Graziano, Ricardo; Dastager, Syed G.; Perez-Gonzalez, Graciela Lizeth; Bogdanchikova, Nina; Iglesias, Ana Leticia; Villarreal-Gomez, Luis Jesus (Applied Microbiology and Biotechnology, 2025)
A wide array of pharmaceutical and industrial products available in today's market stems from bioreactors. Meeting the escalating demand for these products necessitates significant enhancements in biotechnological processes. This study focuses on developing cost-effective scaffolds designed explicitly for use within bioreactors, employing commonly used polymers such as gelatin and collagen. Bacterial proliferation assays involving Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa were conducted to assess the effectiveness of these scaffolds. The scaffolds were produced by electrospinning polymeric solutions with varying concentrations of gelatin and collagen and were characterized using scanning electron microscopy, Fourier transform infrared spectroscopy, differential scanning calorimetry, and thermogravimetric analysis. Results revealed that scaffolds with 15% gelatin increased the 24-h proliferation of S. aureus, P. aeruginosa, and E. coli by 52%, 35%, and 20%, respectively. In the case of E. coli, scaffolds with lower gelatin concentrations (1-10%) were more effective, leading to 35-55% proliferation growth. These findings highlight the potential application of gelatin/collagen scaffolds in fabricating industrial products derived from these bacteria.
Keywords: Bacterial cell proliferation; collagen; gelatin; Polymeric electrospinning; scaffolds